Synthesis of DL-Hydroxybenzenamides as Anticonvulsants - Meza-Toledo, Sergio E; Yasutake-Kimoto, Liliana; Alcalá-Rentería, Martha; Domínguez-Rodríguez, Miguel A; Jaime-Rodriguez, Rodrigo; Nava-Arzaluz, Maria G; Gutiérrez-Laflor, Giovanna; Peralta-Cruz, Javier; Carvajal-Sandoval, Guillermo (Arzneimittelforschung, 2008)
The anticonvulsant activity of some DL-hydroxybenzenamides is described. The following compounds from this series were prepared and tested: DL-2-hydroxy-2-(3’-bromophenyl)butyramide (4, CAS 620950-12-1), DL-2-hydroxy-2-(4’-bromophenyl)butyramide (5, CAS 620950-13-2), DL-2-hydroxy-2-(3’-nitrophenyl)butyramide (6, CAS 620950-14-3), DL-2-hydroxy-2-phenyl hexanamide (7, CAS 63002-05-1), DL-2-hydroxy-2-(3’,4’-dichlorophenyl)hexanamide (8, CAS 863976-06-1), DL-3-hydroxy-3-(4’-bromophenyl)pentanamide (9, CAS 620950-16-5), DL-3-hydroxy-3-phenylheptanamide (10, CAS 863976-08-3) and DL-4-hydroxy-4-(4’-bromophenyl)hexanamide (11, CAS 620950-18-7). Compounds 4, 5, 9 and 11 exhibited significant activity in seizures induced by pentylenetetrazol. Incorporation of bromine in the phenyl ring increased their potency. Compounds 4, 5, 9 and 11 exhibited a similar anticonvulsant activity as the reference drug phenobarbital (CAS 50-06-6).
Keywords: Anticonvulsants; Antiepileptics; DL-Hydroxybenzenamides, anticonvulsant activity, synthesis